1990
DOI: 10.1083/jcb.111.3.919
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the state of actin during the exocytotic reaction of permeabilized rat mast cells.

Abstract: Abstract. The major part of mast cell actin is Tritonsoluble and behaves as a monomer in the DNase I inhibition assay. Thus, actin exists predominantly in monomeric or short filament form, though filamentous actin is clearly apparent in the cortical region after rhodamine-phalloidin (RP) staining. The minimum actin content is estimated to be ~2.5/~g/106 cells (cytosolic concentration ~110 #M.After permeabilization of mast cells by the bacterial cytolysin streptolysin-O, *60% of the Triton-soluble actin leaks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 43 publications
(51 reference statements)
10
96
0
Order By: Relevance
“…Immunofluorescence and cytochemical studies demonstrated that F-actin is localized mainly in the cortical region of chromaffin cells (Vitale et al 1991(Vitale et al , 1995 or mast cells (Koffer et al 1990) in the resting state. In the case of cultured normal anterior pituitary cells (Carbajal & Vitale 1997) and pituitaryderived GH4C1 cells (Kiley et al 1992), these cells exhibited bright cortical actin staining, but in GH3B6 cells, the staining was diffuse in the cytoplasm and displayed a patchy aspect at the cell periphery (van de Moortele et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence and cytochemical studies demonstrated that F-actin is localized mainly in the cortical region of chromaffin cells (Vitale et al 1991(Vitale et al , 1995 or mast cells (Koffer et al 1990) in the resting state. In the case of cultured normal anterior pituitary cells (Carbajal & Vitale 1997) and pituitaryderived GH4C1 cells (Kiley et al 1992), these cells exhibited bright cortical actin staining, but in GH3B6 cells, the staining was diffuse in the cytoplasm and displayed a patchy aspect at the cell periphery (van de Moortele et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…FcεRI aggregation triggers cortical F-actin disassembly, which allows access of the secretory vesicles to the plasma membrane (1,8,23,28,34). The process of F-actin disassembly was shown to be dependent on the increase of intracellular Ca 2ϩ (16,23). On the other hand, a powerful regulator of Ca 2ϩ entry and exocytosis in MCs is the serum-and glucocorticoidinducible kinase SGK1 (9,10,33).…”
Section: Mcs and Sgk1mentioning
confidence: 99%
“…No accumulation of F-actin was apparent at the level of cell attachment or at any other plane. Flow cytometric determinations of cellular F-actin content were performed on suspended RP-stained cells as described previously (Koffer et al, 1990).…”
Section: Image Analysismentioning
confidence: 99%